Upaya Kepolisian Dalam Pencegahan Kejahatan Judi Online (Studi Kasus Judi Slot) - Ahmad Syafikri Alkarni; Taun Taun (Peneliti.net, 2023)
Gambling has existed since time immemorial when human civilization developed. The Encyclopedia Britanica notes that gambling has been found since primitive times, for example Bushmen in South Africa, Aborigines in Australia and Indians in America, where they have known the game of dice. Gambling is essentially an act that is very contrary to religious norms, morality, decency and legal norms. So it can be said that gambling is actually not getting benefits but rather suffering and suffering even more. The implementation of Law Number 19 of 2019 concerning Information and Electronic Transactions cannot be separated from the implementation of other laws or regulations. Because this Law only qualifies criminal acts and carries out threats against perpetrators of criminal acts, and some special meanings (for example the definition of documents electronics, telecommunications).